Plats för välbefinnande - rummets påverkan på känslor, syn på välbefinnande och meningen med livet. - Tähtinen,Lotta; Lundell,Andreas (2019)
We are constantly moving between environments that are designed to affect us in one way or another. The purpose of this study is to investigate if the room has an influence on people's feelings, and their views on well-being and meaning of life. In a randomised experiment, the study explores whether there is a measurable difference in the participants’ feelings and thoughts in a church (n=51) and a shopping mall (n=51). In this study, open-ended questions with word responses (semantic measures) are used together with Positive and Negative Affect Schedule (PANAS) to measure participants’ feelings. Frequentist statistics and artificial intelligence were used to analyse the data. Analyses of the semantic measures showed that words written in the church had a significantly more positive valence than words written in the shopping mall (t=-3,17, p=,002, two-tailed, Cohen’s D=0,63), and that the participants’ word responses for feelings differed significantly with a large effect size (t=5.43, p=,001, Cohen’s D=0.76). PANAS did not show any significant difference in the participants’ positive (t(102) =1,82, p=,072, one-tail, Cohens D=0,37) or negative feelings (t (102) =-1,64, p=,103, one-tailed, Cohens D=0,26). This study indicates that the rooms we spend time in has an effect on our feelings.
Keywords: feelings; rooms; semantic measures; PANAS; well-being; meaning of life; artificial intelligence; AI; känslor; rum; semantiska mått; välmående; meningen med livet